Some aspects of the recovery of the harm caused to territorial community of the city. - Червенко, А. Г. (Theory and practice of jurisprudence, 2016)
We consider the problem of inconsistency of Kharkiv City Council decision to Ukrainian legislation. Focus is made on the legal analysis of this regulatory act. The practical need to change the above mentioned decision in order to make in conformity with Ukrainian legislation is substantiated.